Marine algae of St. Martin’s Island, Bangladesh. XII. New records of red and green algae - Aziz, Abdul; Rahman, Md Towhidur (Bangladesh Journal of Botany, 2011)
Ceramium tenerrimum (G. Martens) Okamura fa, Caulerpa sertularioides fa corymbosa Taylor and Cladophora vagabunda (L.) Hoek from St. Martin’s Island, Bangladesh have been recorded, and described and illustrated for the first time with descriptions and illustrations. Key words: Ceramium; Caulerpa; Cladophora; Red alga; Green algae; Bangladesh DOI: http://dx.doi.org/10.3329/bjb.v40i1.7996 Bangladesh J. Bot. 40(1): 41-45, 2011 (June)